Collagenase H is Crucial for Isolation of Rat Pancreatic Islets. Issue 10 (October 2014) - Fujio, Atsushi; Murayama, Kazutaka; Yamagata, Youhei; Watanabe, Kimiko; Imura, Takehiro; Inagaki, Akiko; Ohbayashi, Naomi; Shima, Hiroki; Sekiguchi, Satoshi; Fujimori, Keisei; Igarashi, Kazuhiko; Ohuchi, Noriaki; et al.
The role(s) of collagenase G (ColG) and collagenase H (ColH) during pancreatic islet isolation remains controversial, possibly due to the enzyme blends used in the previous studies. We herein examined the role of ColG and ColH using highly pure enzyme blends of recombinant collagenase of each subtype. Rat pancreases were digested using thermolysin, together with ColG, ColH, or ColG/ColH ( n = 9, respectively). No tryptic-like activity was detected in any components of the enzyme blends. The efficiency of the collagenase subtypes was evaluated by islet yield and function. Immunohistochemical analysis, in vitro collagen digestion assay, and mass spectrometry were also performed to examine the target matrix components of the crucial collagenase subtype. The islet yield was highest in the ColG/ColH group (4, 101 ± 460 islet equivalents). A substantial number of functional islets (2, 811 ± 581 islet equivalents) was obtained in the ColH group, whereas no islets were retrieved in the ColG group. Mass spectrometry demonstrated that ColH reacts with collagen I and III. In the immunohistochemical analysis, both collagen I and III were located in exocrine tissues, although collagen III expression was more pronounced. The collagen digestion assay showed that collagen III was more effectively digested by ColH than by ColG. The present study reveals that ColH is crucial, while ColG plays only a supporting role, in rat islet isolation. In addition, collagen III appears to be one of the key targets of ColH.